Violence against women: prevalence and associated factors in patients attending a public healthcare service in the Northeast of Brazil Violência contra a mulher: prevalência e fatores associados em pacientes de um serviço público de saúde no Nordeste brasileiro - Maria Arleide da Silva; Gilliatt Hanois Falbo Neto; José Natal Figueiroa; José Eulálio Cabral Filho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The prevalence of and factors associated with violence against women attended as outpatients between October 2005 and January 2006 by the Instituto Materno Infantil Professor Fernando Figueira (IMIP), Recife, Pernambuco State, Brazil, were investigated using a cross-sectional type study. 619 women over the age of 18 were included in a systematic probabilistic sample. The modified Abuse Assessment Screen (AAS) was applied and the data were evaluated statistically by way of univariate and bivariate analyses, using the χ2 or Fischer's exact test and an adjusted multivariate logistic regression model. The prevalence of violence against women was 27.5% (95%CI: 24.0%-31.2%) in the twelve-month period prior to the consultation. The associated factors were low level of schooling (OR = 2.34), a history of domestic violence (OR = 2.21) the woman being mentally disturbed (OR = 2.35), and the partner's consumption of alcohol (OR = 1.77). The prevalence of violence was high in the group of women studied, indicating the need to broaden preventive measures and all-round health care for women. Investigou-se a prevalência e os fatores associados à violência contra mulheres assistidas no ambulatório do Instituto Materno Infantil Prof. Fernando Figueira (IMIP), Recife, Pernambuco, Brasil, utilizando um estudo tipo corte transversal (Outubro/2005 a Janeiro/2006). Foram incluídas 619 mulheres com idade > 19 anos, sendo a amostra probabilística sistemática. Utilizou-se o instrumento Abuse Assessment Screen(AAS), modificado. Os dados foram avaliados estatisticamente por análise uni e bivariada, usando-se o teste χ2 ou exato de Fischer e um modelo ajustado de regressão logística multivariada. Foi de 27,5% (IC95%: 24,0%-31,2%) a prevalência de violência contra a mulher nos últimos 12 meses. Os fatores associados foram baixa escolaridade (OR = 2,34), historia de violência familiar (OR = 2,21), transtorno mental da mulher (OR = 2,35) e uso de bebida alcoólica pelo parceiro(OR = 1,77). Foi elevada a prevalência de violência contra a mulher no grupo estudado, indicando a necessidade de ampliar a prevenção e os cuidados à saúde integral da mulher.